Budget Programs and Performance away to enhance the control in government economic units - عبد الله, سلمان حسين (Journal of Economics and Administrative Sciences, 2016)
The control function of important functions in the system of government for several reasons , perhaps the most important of the magnitude of spending and spending in one of the tools adopted in the implementation of the control function.                                        Perhaps the most prominent stages of the development budget in terms of setup and use in the budget programs and performance , as specialized literature  show its importance in strengthening financial and operationl control over the government transactions though its dependence on the formation of the programs you want governmant units the promote implementation and asset of performance standards that can be adopted on the subject of evaluating the performance of personnel and units in general package.                                                                 This study has reached a set of conclusions we will mention the most important:That the style of the budget programs and performance is based reclassification of public expenditure so that matdzh units of government show business and matqon activities and though the indentification of costs and there by to reduce cost , as well as help to complete the process of effective control and pay attention to what has been accomplished .                                                   The study has find the following  :       1-  Application programs need to adopt the budget programe and performance by the ministry of public and accounting service in the preparation of the state budget because they are based on scientific foundation and the process of the preparation of estimates which achieve the objectives of future programs and impose controls on government spending.                                           2- To achieve the first and the most important functions of the budget position which is planning and control must be converted from traditional programs to balance the budget and programe and performance where traditional budget.